Compassion fatigue, burnout, compassion satisfaction and depression among emergency department physicians and nurses: a cross-sectional study - Ying Zhong; Huan Ma; Shuang Quan Huang; Bo We (BMJ Open, 2022)
Objectives Emergency department physicians and nurses are at high risk of compassion fatigue, burnout and depression. The purpose of this study was to examine the inter-relationship between compassion fatigue, burnout, compassion satisfaction and depression in emergency department physicians and nurses.Design A cross-sectional study.Setting This study was conducted in five tertiary hospitals in five different cities across the province of Sichuan, China, in 2021.Participants A total of 342 emergency department physicians and nurses participated in the study.Main outcome measures Compassion fatigue, burnout, compassion satisfaction and depression scores.Results Among the study participants, 100% were found to have depressive symptoms, 27.8% had low compassion satisfaction, 2.3% had high burnout and 3.8% had compassion fatigue. In the final multiple linear regression model, marital status (p=0.008; 95% CI –5.205 to –0.789), history of chronic disease (p=0.003; 95% CI –6.461 to –1.386), compassion satisfaction (p<0.001; 95% CI 0.593 to 1.274), burnout (p=0.019; 95% CI 0.084 to 0.930) and compassion fatigue (p<0.001; 95% CI –1.527 to –1.053) among emergency department physicians and nurses were considered to be significant predictors of depression.Conclusions The prevalence of depression among emergency department physicians and nurses is high in the province of Sichuan, China. Compassion fatigue, burnout and compassion satisfaction were significantly associated with depression in emergency department physicians and nurses. Hospital administrations should consider these findings to develop appropriate psychological interventions and strategies, to prevent, alleviate or treat severe depression among emergency department physicians and nurses in the province of Sichuan.